How I Might Have Become a Composer - Cherney, Brian (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
Brian Cherney reflects on his childhood and youth in Peterborough, Ontario, in the 1940s and 1950s and his musical studies at the University of Toronto. He considers the varied influence that family, recordings, CBC broadcasts, attending live concerts, piano lessons, reading about music, and spending time in Europe in the late 1960s had in shaping his emerging interest in becoming a composer. Cherney considers that it was only in the mid-1970s, after his appointment to McGill in 1972, that he developed the self-awareness, critical insight, and confidence to become a mature composer … someone who dared, in T.S. Eliot’s words, to “disturb the universe.”